2023
DOI: 10.1021/acs.macromol.3c00966
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition of the Surface Monolayer of Polystyrene Films: Effect of Thermal Preannealing

Abstract: In a previous experiment, we observed that the glass transition temperature of the surface monolayer glass transition temperature (T g surf ) of unannealed polystyrene (PS) films spin-coated on oxide-coated silicon decreased with decreasing film thickness (h < ∼60 nm). However, this h dependence could be removed by thermal preannealing. In this experiment, we investigated the origin of this preannealing effect. We found that T g surf of the thin films increased with preannealing time (t ANN ) and reached the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Since the model of McCaig et al 214 was introduced, different experimental efforts have been devoted to the application of variously developed FVHD models to describe physical aging of thin polymer films, 197,215,216 and polymer nanocomposites. 217,218 Furthermore, the FVHD model was also successfully applied to the description of vitrification kinetics, specifically the previously discussed T g depression with reducing sample size, in polymer thin films, 197,[219][220][221][222][223] and metallic glasses with micrometric size. 190 An important aspect highlighted in all these studies concerns the importance of free unburied sample surface to allow free volume holes to diffuse out of the sample and maintain equilibrium, thus delaying vitrification to lower temperatures; or to recover it once in the glassy state.…”
Section: Physical Aging Dependence On Sample Sizementioning
confidence: 99%
“…Since the model of McCaig et al 214 was introduced, different experimental efforts have been devoted to the application of variously developed FVHD models to describe physical aging of thin polymer films, 197,215,216 and polymer nanocomposites. 217,218 Furthermore, the FVHD model was also successfully applied to the description of vitrification kinetics, specifically the previously discussed T g depression with reducing sample size, in polymer thin films, 197,[219][220][221][222][223] and metallic glasses with micrometric size. 190 An important aspect highlighted in all these studies concerns the importance of free unburied sample surface to allow free volume holes to diffuse out of the sample and maintain equilibrium, thus delaying vitrification to lower temperatures; or to recover it once in the glassy state.…”
Section: Physical Aging Dependence On Sample Sizementioning
confidence: 99%
“…84 Such an irreversibly adsorbed layer has the potential to even perturb the T g of the surface monolayer in the polymer film. Yan et al 85 showed that the confinement effect observed for surface monolayer T g (T g surf ) in PS thin films could be eliminated by performing thermal preannealing. The adsorption kinetics of polymer chains matched well with the time required for the saturation of T g surf value to the thick film T g .…”
Section: ■ Relevant Aspects In Confined Glassy Polymer Films Glass Tr...mentioning
confidence: 99%